Marine sediments microbes capable of electrode oxidation as a surrogate for lithotrophic insoluble substrate metabolism - Rowe, Annette R.; Chellamuthu, Prithiviraj; Lam, Bonita; Okamoto, Akihiro; Nealson, Kenneth H. (Frontiers in Microbiology, 2015)
Little is known about the importance and/or mechanisms of biological mineral oxidation in sediments, partially due to the difficulties associated with culturing mineral-oxidizing microbes. We demonstrate that electrochemical enrichment is a feasible approach for isolation of microbes capable of gaining electrons from insoluble minerals. To this end we constructed sediment microcosms and incubated electrodes at various controlled redox potentials. Negative current production was observed in incubations and increased as redox potential decreased (tested -50 to -400 mV vs Ag/AgCl). Electrode-associated biomass responded to the addition of nitrate and ferric iron as terminal electron acceptors in secondary sediment-free enrichments. Elemental sulfur, elemental iron and amorphous iron sulfide enrichments derived from electrode biomass demonstrated products indicative of sulfur or iron oxidation. The microbes isolated from these enrichments belong to the genera Halomonas, Idiomarina, Marinobacter, and Pseudomonas of the Gammaproteobacteria, and Thalassospira and Thioclava from the Alphaproteobacteria. Chronoamperometry data demonstrates sustained electrode oxidation from these isolates in the absence of alternate electron sources. Cyclic voltammetry demonstrated the variability in dominant electron transfer modes or interactions with electrodes (i.e., biofilm, planktonic or mediator facilitated) and the wide range of midpoint potentials observed for each microbe (from 8 to -295 mV vs. Ag/AgCl). The diversity of extracellular electron transfer mechanisms observed in one sediment and one redox condition, illustrates the potential importance and abundance of these interactions. This approach has promise for increasing our understanding the extent and diversity of microbe mineral interactions, as well as increasing the repository of microbes available for electrochemical applications.